Platinum salt sensitivity in refinery workers: incidence and effects of smoking and exposure. Issue 10 (October 1995) - Calverley, A E; Rees, D; Dowdeswell, R J; Linnett, P J; Kielkowski, D
Abstract : OBJECTIVE–To measure the incidence of platinum salt sensitivity (PSS) in refinery workers and examine the influence of cigarette smoking and exposure to platinum salts on sensitisation. DESIGN–A prospective cohort study with examination of workers at quarterly intervals for 18 months, and again at 24 months. SETTING–A South African primary platinum refinery. SUBJECTS–78 new recruits, selected by the refinery's usual procedure, without apparent atopy and in good respiratory health. RESULTS–After 24 months 32 (41%) subjects had been diagnosed PSS and were subsequently medically separated. Twenty two (28%) cases were confirmed by positive skin prick test to platinum salts, 10 (13%) cases were symptomatic but skin prick negative. Incidence of cases per 100 person-months was 1.9 skin prick positive and 0.8 negative. Risk of sensitisation was about eight times greater for smokers than non-smokers, and six times greater for high exposure than low exposure. CONCLUSION–Smoking and intensity of exposure were definitely associated with development of PSS. Positive responses to platinum salt skin prick test had a 100% positive predictive value for symptoms and signs of PSS if exposure continued.